0929 Caregiver-Reported Versus Clinician-Documented Child Sleep Problems and Sleep-Related Health Behaviors in Primary Care. (27th May 2020) - Williamson, A A; Bhandari, E; Cicalese, O; Heaps, E; Ostan, A; Collins, M; Lupini, F; Mindell, J A
Abstract: Introduction: Sleep problems are highly prevalent in early childhood but often under-identified in pediatric primary care. This study identified the prevalence of caregiver-reported versus primary care provider (PCP)-documented sleep problems and sleep-related health behaviors in young children presenting to well child visits (WCVs). Methods: Caregivers (85.4% mothers) of 198 young children (2-5 years, M = 3.3, 53.7% female, 62.9% Black) presenting to urban (74.1%) and suburban (25.9%) primary care sites for well child visits (WCVs) completed research surveys on child behavioral sleep problems, snoring, and sleep-related health behaviors (e.g., caffeine consumption) on the day of their child's WCV. Electronic medical record review was used to identify the rate of PCP-documented sleep problems and related recommendations in the WCV progress note. Results: Fifteen percent of caregivers reported a child sleep problem according to questionnaire data, which did not significantly differ from the 12.0% of children with a PCP-documented sleep problem in the WCV progress note (p = .31). However, significantly more caregivers (28.3%) reported bedtime difficulties (resistance; tantrums) on questionnaires (p <.001), which were not captured in the 12.0% of WCVs noting sleep problems. A total of 8% of WCVs included child sleep recommendations. Child snoring was reported by 17.0% of caregivers, but was less frequently documented in WCVs (4.5%, p <.001). Although many caregivers reported poor child sleep-related health behaviors, including daily child caffeine consumption (21.1%) and bedroom electronics (62.9%), significantly fewer PCPs documented these issues (caffeine: 2.0%; electronics: 6.6%) or related recommendations (decrease caffeine: 1.0%; eliminate electronics: 3.5%) in the progress note (all p-values <.001). Conclusion: Although caregiver-endorsed child sleep problems on surveys did not differ from PCP-documented concerns, there are gaps in documenting other problematic sleep-related health behaviors, such as caffeine consumption and electronics use. More resources to address sleep-related health behaviors, as well as sleep problems, in pediatric primary care are needed. Support: Sleep Research Society Foundation and K23HD094905 (AAW)